2020
DOI: 10.1038/s41598-020-60715-x
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Conducting Polymer Nanotube-based Liquid-Ion Gated Field-Effect Transistor Aptasensor for Dopamine Exocytosis

Abstract: In this study, ultrasensitive and precise detection of a representative brain hormone, dopamine (DA), was demonstrated using functional conducting polymer nanotubes modified with aptamers. A high-performance aptasensor was composed of interdigitated microelectrodes (IMEs), carboxylated polypyrrole nanotubes (CPNTs) and DA-specific aptamers. The biosensors were constructed by sequential conjugation of CPNTs and aptamer molecules on the IMEs, and the substrate was integrated into a liquid-ion gating system surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Figure 2a displays SEM images of the FET system before and after conjugation of anti-cortisol IgG, respectively. The SEM images show that the bare PPy NT with a~200 nm diameter was synthesized with very homogeneous surface morphologies (left image in Figure 2a) [24]. Functionalization of anti-cortisol IgG on the PPy NT surface was also confirmed (right image in Figure 2a).…”
Section: Characterization Of Ppy Nt Fet Transducermentioning
confidence: 77%
“…Figure 2a displays SEM images of the FET system before and after conjugation of anti-cortisol IgG, respectively. The SEM images show that the bare PPy NT with a~200 nm diameter was synthesized with very homogeneous surface morphologies (left image in Figure 2a) [24]. Functionalization of anti-cortisol IgG on the PPy NT surface was also confirmed (right image in Figure 2a).…”
Section: Characterization Of Ppy Nt Fet Transducermentioning
confidence: 77%
“…Another FET was functionalized with carboxylated polypyrrole nanotubes/aptamer and used to detect the dopamine secreted by living cells [149]. A very low detection limit of 100 pM was obtained, as well as a linear range going from 0.1 nM to 10 µM and a high selectivity since catechol, epinephrine, and ascorbic acid did not interfere with dopamine sensing.…”
Section: Graphenementioning
confidence: 99%
“…Controlling the diameter of CPNTs was an important feature, which the authors took into account while constructing this device. It was reported that the small structures demonstrated higher sensitivity and specificity in comparison to the wider ones since they delivered a large available area [ 156 ].…”
Section: Surface Modification and Functionalization Of Chem/biofetsmentioning
confidence: 99%